Workload, Competency, Work Motivation and Their Effect on Employee Performance at the Small Industrial Clushter of Wood Processed in Madiun Regency - Arga Christian Sitohang; Tri Andjarwati; Hendy Widiastoeti (IJEBD (International Journal of Entrepreneurship and Business Development), 2022)
Purpose: This paper aims to explain Workload, Competencies, Work Motivation and Its Effect on Employee Performance at the Small Processed Wood Industrial Center in Madiun Regency.. Design/methodology/approach: Research models with the development of hypotheses are derived based on literature. To provide empirical evidence, researchers conducted a survey, primary data was collected using questionnaire lists, and saturated sampling of 60 employees. Findings: The results showed that each variable of Workload, Competence, and Work Motivation had a positive and significant effect on Employee Performance at the Processed Wood Small Industrial Center in Madiun Regency. Practical implications: The implication of the research is to examine the perceptions of 60 employees at the Processed Wood Small Industrial Center in Madiun Regency. The analytical technique used is multiple linear regression.. Originality/value: This paper is original. Paper type: Is categorized as a research paper.